2012
DOI: 10.1183/09031936.00185511
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of unexpected oxidative stress in airways of adolescents born very pre-term

Abstract: Prematurity and its main respiratory complication, bronchopulmonary dysplasia (BPD), are potentially associated with lifelong respiratory morbidities and/or lung function abnormalities. The mechanisms behind these long-term respiratory problems are still unclear.We assessed airway oxidative stress in adolescents born very pre-term (f32 gestational weeks) by measuring 8-isoprostane concentration in exhaled breath condensate (EBC). In addition, the study protocol included spirometry and measurement of exhaled ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
76
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 42 publications
10
76
2
3
Order By: Relevance
“…Such data support the hypothesis that airflow limitation in BPD survivors is unrelated to any asthma-like inflammation [16,19], indicating that another pathogenetic mechanism must be involved [19,20]. Recent reports have also suggested that prematurity may be associated with neutrophilic airway inflammation and oxidative stress later in life [21,22,23]. Available data thus support the hypothesis that the pathophysiological mechanisms behind airflow limitation in BPD and asthma probably stem from distinct mechanisms which need to be further investigated [24].…”
Section: Clinical Aspects and Functional Course Of Bpd With Agesupporting
confidence: 71%
“…Such data support the hypothesis that airflow limitation in BPD survivors is unrelated to any asthma-like inflammation [16,19], indicating that another pathogenetic mechanism must be involved [19,20]. Recent reports have also suggested that prematurity may be associated with neutrophilic airway inflammation and oxidative stress later in life [21,22,23]. Available data thus support the hypothesis that the pathophysiological mechanisms behind airflow limitation in BPD and asthma probably stem from distinct mechanisms which need to be further investigated [24].…”
Section: Clinical Aspects and Functional Course Of Bpd With Agesupporting
confidence: 71%
“…hyperoxia; lung development; premature birth BRONCHOPULMONARY DYSPLASIA (BPD) is the most common chronic lung disease of very preterm infants. BPD interrupts lung development and has serious long-term respiratory complications that reach beyond childhood and into adult life (8,25,26,41,53). The multifactorial etiology of BPD has prompted research to investigate the many factors contributing to the pathogenesis of BPD (reviewed in Ref.…”
mentioning
confidence: 99%
“…Recent evidence shows that BPD has long-term respiratory complications, which reach beyond childhood and into adult life, with follow-up studies demonstrating increased risk of respiratory symptoms (i.e., cough, wheeze), poor lung function, and low exercise capacity (8,18,25,26,41,53,69). Therefore, longterm studies in experimental models are now gaining greater interest.…”
mentioning
confidence: 99%
“…Many studies have shown that inflammatory markers are elevated in children diagnosed with BPD as neonates. Increased 8-isoprostane levels were detected in the exhaled breath condensate in adolescents born at Յ32 wk of gestation (12). Abnormalities in pulmonary function tests also persist (13,46).…”
mentioning
confidence: 88%